Suicide, Stigma, and Utilizing Social Media Platforms to Gauge Public Perceptions - Nathan, Nila A.; Nathan, Kalpana I. (Frontiers in Psychiatry, 2020)
Background: Suicide, a multifaceted complex outcome that arises from numerous biopsychosocial factors, is a public health concern which is growing in numbers despite valiant prevention efforts. There is still a lot of stigma surrounding suicide that needs to be addressed. Social media is growing exponentially and there are many forums where suicidality is being discussed. Methods: An anonymous and voluntary survey was sent out on the social media platforms of Facebook and Reddit to collect data about perceptions on suicide using surveymonkey.com. It was posted for a week and received 152 responses. Results: Of the 152 respondents, 86% believed that suicide is preventable, and 72.85% believed that it a person’s right to die by suicide. About a third (31.79%) had lost someone close to them to suicide. Respondents who did not think suicide was preventable also viewed suicide as either a sign of strength (42.86%) or a revenge act (33.3%). Those who responded that someone close to them died by suicide believed that the media glorified suicide (56.25%) while those who did not lose someone, did not believe that (66.99%). Women (61%) found social media to be a good platform for people to ask for help while men did not (60.61%). Conclusions: We utilized the social media platforms to gauge the perception of suicide and found that suicide is not as stigmatized, most believed it is preventable, and it is a person’s right to die by suicide. However, there is still room for improvement. There needs to be more education of the media on the effects of glorifying and martyring those who die by suicide. Communities should implement programs that provide more awareness on suicide prevention methods. Because our research showed that many people believe it is a good idea to seek help from social media platforms, machine learning algorithms need to be implemented as much as possible to create a safer space online.